Obstructive Sleep-Disordered Breathing Is More Common than Central in Mild Familial Dysautonomia - Hilz, Max-Josef; Möller, Sebastian; Buechner, Susanne; Czarkowska, Hanna; Ayappa, Indu; Axelrod, Felicia B.; Rapoport, David M. (Journal of Clinical Sleep Medicine, 2016)
In familial dysautonomia (FD) patients, sleep-disordered breathing (SDB) might contribute to their high risk of sleep-related sudden death. Prevalence of central versus obstructive sleep apneas is controversial but may be therapeutically relevant. We, therefore, assessed sleep structure and SDB in FD-patients with no history of SDB.11 mildly affected FD-patients (28 ± 11 years) without clinically overt SDB and 13 controls (28 ± 10 years) underwent polysomnographic recording during one night. We assessed sleep stages, obstructive and central apneas (>= 90% air flow reduction) and hypopneas (> 30% decrease in airflow with >= 4% oxygen-desaturation), and determined obstructive (oAI) and central (cAI) apnea indices and the hypopnea index (HI) as count of respective apneas/hypopneas divided by sleep time. We obtained the apnea-hypopnea index (AHI4%) from the total of apneas and hypopneas divided by sleep time. We determined differences between FD-patients and controls using the U-test and within-group differences between oAIs, cAIs, and HIs using the Friedman test and Wilcoxon test.Sleep structure was similar in FD-patients and controls. AHI4% and HI were significantly higher in patients than controls. In patients, HIs were higher than oAIs and oAIs were higher than cAIs. In controls, there was no difference between HIs, oAIs, and cAIs. Only patients had apneas and hypopneas during slow wave sleep.In our FD-patients, obstructive apneas were more common than central apneas. These findings may be related to FD-specific pathophysiology. The potential ramifications of SDB in FD-patients suggest the utility of polysomnography to unveil SDB and initiate treatment.A commentary on this article appears in this issue on page 1583.
EVALuna2:22543